Pengaruh Teknologi Informasi, Saling Ketergantungan terhadap Karakteristik Informasi Sistem Akuntansi Manajemen (Broad Scope) dan Kinerja Manajerial pada PT Anugrah Dwimitra B.L. Jakarta - Sri Hastuti (Jurnal Aplikasi Manajemen, 2012)
Computer is part of information technology that most used for information system organization. So, the company must read all information technology development, and adopt it if they people do working. The information technology much help people to upgrade they performance, because information technology made they responsibility lightly, and it provide trusted information, complete, and it knows and tested that used to decide and control policy of PT. Anugrah Dwimitra B.L. PT. Anugrah Dwimitra B.L is one of delivery service industry that have used information system technology where the system have not yet much help anymore. So, this research want to know how the influence and the dependence of management accountant information (broadscope) and management performance. The researcher use primary data that have got from respondent who fill some questioner. There are 17 manager that I use as the population of research, determining sample adopt sensus technique. The data analyzed by path analyzed technique.The research show that information technology have not direct influence to management performance, it have positive influence through broadscope, and dependence have not influence to management performance through broadscope and broadscope have not influence to management performance.Keywords: Information Technology, Dependence, Broadscope, Management Performance